SimilarityTS: Toolkit for the evaluation of similarity for multivariate time series - Alejandro Fernández-Montes; Damián Fernández-Cerero; Felipe Escalera-González; Agnieszka Jakóbik; Belén Bermejo; Carlos Juiz (SoftwareX, 2023)
This paper presents SimilarityTS, a toolkit for the evaluation of similarity for multivariate time series. This software enables the comparison and assessment of the similarity between time series in a standard way, using the most relevant metrics and figures usually employed in the literature, such as the Kullback–Leibler divergence, Dynamic Time Warping, DTW paths, PCA, and t-SNE representations, among others. This toolkit provides a better way to compare research results and facilitates the repeatability of experiments.